Teologi Sosial-Kebangsaan KH. Hasyim Asy’ari (Analisis Kritis Resolusi Jihad dan Muqaddimah Qanun Assasi) - Zifamina, M. Ikhbar Fiamrillah (Indonesian Journal of Islamic Theology and Philosophy, 2025)
Abstract This article aims to discuss the theological thinking of KH. Hasyim Asy'ari in the context of social nationality. The social-national theology can be traced in Jihad Resolution, Muqaddimah Qanun Asasi and theological criticism in some of his works. The method in this research is the critical analysis method, which is to examine the concept of KH. Hasyim Asy'ari's socio-national theology in these works. The urgency of this research is to review the theological thinking of KH. Hasyim Asy'ari in the social and national context so that there is a need to recontextualize Islamic thought based on tawhid and the social-national context taken from the scientific tradition of Indonesian scholars themselves. The findings of this article are: First, the social-national theology of KH. Hasyim Asy'ari in the Jihad Resolution, Muqaddimah Qanun Asasi and theological criticism in the works show the external side of anti-colonialism, and the internal side of the unity of Muslims, Second, the social-national theology of KH. Hasyim Asy'ari shows that Ahlusunnah wal Jama'ah theology in the socio-religious and political-national context can be a relevant theological concept building used to answer contemporary national problems today, especially in terms of unity in the frame of nationality and a vision of humanity based on religion. Keywords: Jihad Resolution; KH. Hasyim Asy'ari; Muqaddimah Qanun Asasi; Socio-National Theology; Theological Criticism.   Abstrak Artikel ini bertujuan untuk membahas tentang pemikiran teologis dari KH. Hasyim Asy’ari dalam konteks sosial kebangsaan. Teologi sosial-kebangsaan tersebut dapat dilacak dalam Resolusi Jihad, Muqaddimah Qanun Asasi dan kritik teologis dalam beberapa karyanya. Metode dalam penelitian ini adalah metode analisis kritis, yakni untuk menelaah konsep teologi sosial-kebangsaan KH. Hasyim Asy’ari dalam karya-karya tersebut. Urgensi penelitian ini adalah meninjau kembali pemikiran teologis dari KH. Hasyim Asy’ari dalam konteks sosial dan kebangsaan sehingga perlu adanya rekontekstualisasi pemikiran Islam yang berbasiskan pada tauhid dan konteks sosial-kebangsaan yang diambil dari tradisi keilmuan ulama-ulama Indonesia itu sendiri. Hasil temuan dari artikel ini yakni: Pertama, teologi sosial-kebangsaan KH. Hasyim Asy’ari dalam Resolusi Jihad, Muqaddimah Qanun Asasi dan kritik teologis dalam karya-karya menujukkan sisi eksternal yang anti kolonialisme, dan sisi internal pada persatuan umat Islam, Kedua, teologi sosial-kebangsaan KH. Hasyim Asy’ari menunjukkan bahwa teologi Ahlusunnah wal Jama’ah dalam konteks sosial-keagamaan dan politik-kebangsaan dapat menjadi bangunan konsep teologis yang relevan digunakan untuk menjawab problem kebangsaan kontemporer saat ini khususnya dalam hal persatuan dalam bingkai kebangsaan dan visi kemanusiaan berbasis pada keagamaan. Kata Kunci: KH. Hasyim Asy’ari; Kritik Teologis; Muqaddimah Qanun Asasi; Resolusi Jihad; Teologi Sosial-Kebangsaan.